6.165 Problems 16401 to 16500

Table 6.329: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

16401

\[ {}y^{\prime \prime \prime \prime }+12 y^{\prime \prime \prime }+60 y^{\prime \prime }+124 y^{\prime }+75 y = 0 \]

16402

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+2 y^{\prime }+6 y = 0 \]

16403

\[ {}y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+30 y^{\prime \prime }-56 y^{\prime }+49 y = 0 \]

16404

\[ {}\frac {31 y^{\prime \prime \prime }}{100}+\frac {56 y^{\prime \prime }}{5}-\frac {49 y^{\prime }}{5}+\frac {53 y}{10} = 0 \]

16405

\[ {}2 y y^{\prime \prime }+y^{2} = {y^{\prime }}^{2} \]

16406

\[ {}y^{\prime \prime \prime }+y^{\prime \prime } = {\mathrm e}^{t} \]

16407

\[ {}y^{\prime \prime \prime \prime }-16 y = 1 \]

16408

\[ {}y^{\left (5\right )}-y^{\prime \prime \prime \prime } = 1 \]

16409

\[ {}y^{\prime \prime \prime \prime }+9 y^{\prime \prime } = 1 \]

16410

\[ {}y^{\prime \prime \prime \prime }+9 y^{\prime \prime } = 9 \,{\mathrm e}^{3 t} \]

16411

\[ {}y^{\prime \prime \prime }+10 y^{\prime \prime }+34 y^{\prime }+40 y = t \,{\mathrm e}^{-4 t}+2 \,{\mathrm e}^{-3 t} \cos \left (t \right ) \]

16412

\[ {}y^{\prime \prime \prime }+6 y^{\prime \prime }+11 y^{\prime }+6 y = 2 \,{\mathrm e}^{-3 t}-t \,{\mathrm e}^{-t} \]

16413

\[ {}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime }+13 y^{\prime \prime }-24 y^{\prime }+36 y = 108 t \]

16414

\[ {}y^{\prime \prime \prime }+6 y^{\prime \prime }-14 y^{\prime }-104 y = -111 \,{\mathrm e}^{t} \]

16415

\[ {}y^{\prime \prime \prime \prime }-10 y^{\prime \prime \prime }+38 y^{\prime \prime }-64 y^{\prime }+40 y = 153 \,{\mathrm e}^{-t} \]

16416

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = \tan \left (2 t \right ) \]

16417

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = \sec \left (2 t \right ) \tan \left (2 t \right ) \]

16418

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime } = \sec \left (2 t \right )^{2} \]

16419

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime } = \tan \left (2 t \right )^{2} \]

16420

\[ {}y^{\prime \prime \prime }+9 y^{\prime } = \sec \left (3 t \right ) \]

16421

\[ {}y^{\prime \prime \prime }+y^{\prime } = -\sec \left (t \right ) \tan \left (t \right ) \]

16422

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = \sec \left (2 t \right ) \]

16423

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime } = -\frac {1}{t^{2}}-\frac {2}{t} \]

16424

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = \frac {{\mathrm e}^{t}}{t} \]

16425

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime }-11 y^{\prime }+30 y = {\mathrm e}^{4 t} \]

16426

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }-10 y^{\prime }-24 y = {\mathrm e}^{-3 t} \]

16427

\[ {}y^{\prime \prime \prime }-13 y^{\prime }+12 y = \cos \left (t \right ) \]

16428

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+2 y^{\prime } = \cos \left (t \right ) \]

16429

\[ {}y^{\left (6\right )}+y^{\prime \prime \prime \prime } = -24 \]

16430

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime } = \tan \left (t \right )^{2} \]

16431

\[ {}y^{\prime \prime \prime }-y^{\prime \prime } = 3 t^{2} \]

16432

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime } = \sec \left (t \right )^{2} \]

16433

\[ {}y^{\prime \prime \prime }+y^{\prime } = \sec \left (t \right ) \]

16434

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime } = \cos \left (t \right ) \]

16435

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime } = t \]

16436

\[ {}t^{2} \ln \left (t \right ) y^{\prime \prime \prime }-t y^{\prime \prime }+y^{\prime } = 1 \]

16437

\[ {}\left (t^{2}+t \right ) y^{\prime \prime \prime }+\left (-t^{2}+2\right ) y^{\prime \prime }-\left (2+t \right ) y^{\prime } = -2-t \]

16438

\[ {}2 t^{3} y^{\prime \prime \prime }+t^{2} y^{\prime \prime }+t y^{\prime }-y = -3 t^{2} \]

16439

\[ {}t y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime } = \frac {45}{8 t^{{7}/{2}}} \]

16440

\[ {}4 x^{2} y^{\prime \prime }-8 x y^{\prime }+5 y = 0 \]

16441

\[ {}3 x^{2} y^{\prime \prime }-4 x y^{\prime }+2 y = 0 \]

16442

\[ {}2 x^{2} y^{\prime \prime }-8 x y^{\prime }+8 y = 0 \]

16443

\[ {}2 x^{2} y^{\prime \prime }-7 x y^{\prime }+7 y = 0 \]

16444

\[ {}4 x^{2} y^{\prime \prime }+17 y = 0 \]

16445

\[ {}9 x^{2} y^{\prime \prime }-9 x y^{\prime }+10 y = 0 \]

16446

\[ {}2 x^{2} y^{\prime \prime }-2 x y^{\prime }+20 y = 0 \]

16447

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+10 y = 0 \]

16448

\[ {}4 x^{2} y^{\prime \prime }+8 x y^{\prime }+y = 0 \]

16449

\[ {}4 x^{2} y^{\prime \prime }+y = 0 \]

16450

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 0 \]

16451

\[ {}x^{2} y^{\prime \prime }+7 x y^{\prime }+9 y = 0 \]

16452

\[ {}x^{3} y^{\prime \prime \prime }+22 x^{2} y^{\prime \prime }+124 x y^{\prime }+140 y = 0 \]

16453

\[ {}x^{3} y^{\prime \prime \prime }-4 x^{2} y^{\prime \prime }-46 x y^{\prime }+100 y = 0 \]

16454

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = 0 \]

16455

\[ {}x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }+6 x y^{\prime }+4 y = 0 \]

16456

\[ {}x^{3} y^{\prime \prime \prime }+2 x y^{\prime }-2 y = 0 \]

16457

\[ {}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }-2 x y^{\prime }-2 y = 0 \]

16458

\[ {}x^{3} y^{\prime \prime \prime }+6 x^{2} y^{\prime \prime }+7 x y^{\prime }+y = 0 \]

16459

\[ {}x^{3} y^{\prime \prime \prime \prime }+6 x^{2} y^{\prime \prime \prime }+7 x y^{\prime \prime }+y^{\prime } = 0 \]

16460

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = \frac {1}{x^{5}} \]

16461

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = x^{3} \]

16462

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = \frac {1}{x^{2}} \]

16463

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = \frac {1}{x^{2}} \]

16464

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 2 x \]

16465

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-16 y = \ln \left (x \right ) \]

16466

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 8 \]

16467

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+36 y = x^{2} \]

16468

\[ {}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }-11 x y^{\prime }+16 y = \frac {1}{x^{3}} \]

16469

\[ {}x^{3} y^{\prime \prime \prime }+16 x^{2} y^{\prime \prime }+70 x y^{\prime }+80 y = \frac {1}{x^{13}} \]

16470

\[ {}3 x^{2} y^{\prime \prime }-4 x y^{\prime }+2 y = 0 \]

16471

\[ {}2 x^{2} y^{\prime \prime }-7 x y^{\prime }+7 y = 0 \]

16472

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 0 \]

16473

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

16474

\[ {}x^{3} y^{\prime \prime \prime }+10 x^{2} y^{\prime \prime }-20 x y^{\prime }+20 y = 0 \]

16475

\[ {}x^{3} y^{\prime \prime \prime }+15 x^{2} y^{\prime \prime }+54 x y^{\prime }+42 y = 0 \]

16476

\[ {}x^{3} y^{\prime \prime \prime }-2 x^{2} y^{\prime \prime }+5 x y^{\prime }-5 y = 0 \]

16477

\[ {}x^{3} y^{\prime \prime \prime }-6 x^{2} y^{\prime \prime }+17 x y^{\prime }-17 y = 0 \]

16478

\[ {}2 x^{2} y^{\prime \prime }+3 x y^{\prime }-y = \frac {1}{x^{2}} \]

16479

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = \ln \left (x \right ) \]

16480

\[ {}4 x^{2} y^{\prime \prime }+y = x^{3} \]

16481

\[ {}9 x^{2} y^{\prime \prime }+27 x y^{\prime }+10 y = \frac {1}{x} \]

16482

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+2 y = 0 \]

16483

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = 0 \]

16484

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = 0 \]

16485

\[ {}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }+37 x y^{\prime } = 0 \]

16486

\[ {}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }-3 x y^{\prime } = 0 \]

16487

\[ {}x^{3} y^{\prime \prime \prime }+x y^{\prime }-y = 0 \]

16488

\[ {}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }-3 x y^{\prime } = -8 \]

16489

\[ {}\left (x^{2}+1\right )^{2} y^{\prime \prime }+2 x \left (x^{2}+1\right ) y^{\prime }+4 y = 0 \]

16490

\[ {}\left (x^{2}+1\right )^{2} y^{\prime \prime }+2 x \left (x^{2}+1\right ) y^{\prime }+4 y = \arctan \left (x \right ) \]

16491

\[ {}\left (x^{2}+1\right )^{2} y^{\prime \prime }+2 x \left (x^{2}+1\right ) y^{\prime }+4 y = 0 \]

16492

\[ {}\left (x^{2}+1\right )^{2} y^{\prime \prime }+2 x \left (x^{2}+1\right ) y^{\prime }+4 y = \arctan \left (x \right ) \]

16493

\[ {}\left (x^{4}-1\right ) y^{\prime \prime }+\left (x^{3}-x \right ) y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

16494

\[ {}\left (x^{4}-1\right ) y^{\prime \prime }+\left (x^{3}-x \right ) y^{\prime }+\left (4 x^{2}-4\right ) y = 0 \]

16495

\[ {}\left (x^{4}-1\right ) y^{\prime \prime }+\left (x^{3}-x \right ) y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

16496

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = 0 \]

16497

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = x^{2} \]

16498

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 0 \]

16499

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

16500

\[ {}x^{3} y^{\prime \prime \prime }+16 x^{2} y^{\prime \prime }+79 x y^{\prime }+125 y = 0 \]